2008
DOI: 10.1017/s1355617708081356
|View full text |Cite
|
Sign up to set email alerts
|

Functional brain organization for visual search in ASD

Abstract: Although previous studies have shown that individuals with autism spectrum disorder (ASD) excel at visual search, underlying neural mechanisms remain unknown. This study investigated the neurofunctional correlates of visual search in children with ASD and matched typically developing (TD) children, using an event-related functional magnetic resonance imaging design. We used a visual search paradigm, manipulating search difficulty by varying set size (6, 12, or 24 items), distractor composition (heterogeneous o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 47 publications
3
53
1
2
Order By: Relevance
“…On the other hand, syntacticsemantic deficits in ASD are much more related to decreased activity of the IFG and increased activity of Wernicke's area, to the use of visual pathways to support language comprehension, and to the presence of reduced or reversed leftward asymmetry. This 'visually-mediated' language processing coexists in these patients with abnormal visuomotor processing, showing a functional overlap between both cognitive processes, where the processing strategy depends to an abnormally large extent on activation of parieto-occipital pathways (Belmonte et al 2010;Belmonte and Yurgelun-Todd 2003;Bolte et al 2008;Damarla et al 2010;Keehn et al 2008;Ring et al 1999;Shukla et al 2010b). The distinction between the syntacticsemantic and semantic-pragmatic component of language has been supported by neuropsychological and neuroimaging studies.…”
Section: Discussionmentioning
confidence: 84%
“…On the other hand, syntacticsemantic deficits in ASD are much more related to decreased activity of the IFG and increased activity of Wernicke's area, to the use of visual pathways to support language comprehension, and to the presence of reduced or reversed leftward asymmetry. This 'visually-mediated' language processing coexists in these patients with abnormal visuomotor processing, showing a functional overlap between both cognitive processes, where the processing strategy depends to an abnormally large extent on activation of parieto-occipital pathways (Belmonte et al 2010;Belmonte and Yurgelun-Todd 2003;Bolte et al 2008;Damarla et al 2010;Keehn et al 2008;Ring et al 1999;Shukla et al 2010b). The distinction between the syntacticsemantic and semantic-pragmatic component of language has been supported by neuropsychological and neuroimaging studies.…”
Section: Discussionmentioning
confidence: 84%
“…However, looking at a target/distracter search task, Keehn et al (2008) found increased activation in individuals on the autism spectrum compared to TD controls in both frontoparietal and occipital regions. This study also found that, while patterns of activation differed for controls between an easy feature search task and a more difficult one, no such differences were found for the autism group.…”
Section: Visual Searchmentioning
confidence: 90%
“…A visual search test revealed greater activation in the visual cortex (also frontoparietal), likely related to enhanced discrimination and increased modulation of visual attention [252]. Finally, Bonilha et al [254] reported that patients with autism showed a decrease in white matter in the visual cortex (as well as the frontal, temporal, and parietal cortex) in association with a generally enlarged cortex.…”
Section: Visual Cortexmentioning
confidence: 97%
“…The same type of hypoperfusion was found in the parents and also the siblings. Keehn et al [252] used event-related fMRI to visual stimuli to show greater activation in frontal (also parieto-occipital) regions in individuals with autism than in controls. The conclusion was that a search efficiency in autism may be related to increased modulation of visual attention.…”
Section: Frontal Cortexmentioning
confidence: 99%